INDONESIA-MALAYSIA DIGITAL TAX TRANSPARENCY: MAQASID SHARIA APPROACH TO TAXPAYER RIGHTS AND JUSTICE - Firdha Nur Alfiani; Shofa Robbani; Lisa Aminatul Mukaromah; Muhammad Nazir Alias (Universitas Muhammadiyah Prof DR HAMKA, 2026)
Research aims: This study examines transparency and taxpayer rights protection in digital tax systems in Indonesia and Malaysia within conventional justice and maqasid sharia frameworks. It addresses the lack of integrated comparative analysis on how digital tax governance aligns with Islamic ethical principles in Muslim-majority countries. Design/Methodology/Approach: Using a qualitative normative-juridical comparative approach, this study analyzes Indonesia’s Core Tax Administration System (e-filing, e-billing, e-faktur) and Malaysia’s MyTax/LHDN Online. Data are drawn from tax regulations, OECD and IMF reports, academic literature, and Islamic legal sources. The analysis applies constitutional justice and maqasid sharia perspectives, focusing on hifdz al-mal and hifdz al-haq across daruriyyat, hajiyyat, and tahsiniyyat. Research findings: Malaysia shows stronger alignment between transparency mechanisms and hifdz al-mal, along with more structured taxpayer protection frameworks. Indonesia demonstrates progress in digitalization but faces challenges in ensuring transparency and rights protection. Both systems reveal limited integration of Islamic ethical principles, with gaps in algorithmic transparency, maqasid-based governance, and institutional coordination. Theoretical Contribution/Originality: This study integrates conventional tax justice theory with maqasid sharia to develop a comparative analytical framework. Practitioners/Policy Implications: It proposes a Maqasid-Based Digital Tax Justice Model to enhance transparency and taxpayer protection in digital tax systems. Research Limitations/Implications: The study is limited to a normative approach and secondary data; future research should incorporate empirical validation and broader comparative contexts.